Simulation of Vibrational Spectra (IR and Raman), PED Analysis and Study of Solvation Effects on Electronic Properties of Methyldopa - Chaudhary, Tarun; Joshi, Bhawani Datt (Api Journal of Science, 2024)
The properties like hydrogen bonding, partial atomic charges associated with atoms and intramolecular charge transfer characteristics of a drug are very crucial for its biological activity. In the paper, these electronic properties of antihypertensive drug methyldopa have been studied intensively, using Density Functional Theory (DFT). The simulated infrared (IR) and Raman spectra of monomer and dimer, Potential energy distribution (PED), Mullikan atomic charges and UV spectra have been analysed. In both IR and Raman spectra, the prominent stretching of the O-H group taking part in intermolecular hydrogen bonding was obtained at 2814.64 cm−1. Furthermore, the most negative Mulliken charge was found to be associated with nitrogen, N5 and onygen, O4 and the most positive with carbon atom C10 in momomer. The UV-Vis absorption spectra analysis has been performed in gaseous and solvent (EtOH) states. The present work precisely explains hydrogen bonding, reactive sites and possibility of intramolecular charge transfer.